Free-radical reactions and thermal effects in PE during pipe extrusion - Özcanli, YL; Mamedov, SV; Aktas, B; Yalçinyuva, T; Alekperov, VA; Yilgin, R; Durmus, A; Öksüz, S (CARL HANSER VERLAG, 2002)
In this study, various effects on the properties of the material, such as free-radical (FR) processes, oxygen induction time (OIT), melting temperature and melting heat are examined during several stages of the polyethylene (PE) pipe extrusion process. The spectra in the Electron Spin Resonance (ESR) are researched between 77-293 K and in a wide range of magnetic fields. At 77 K a triplet signal in ESR is observed. The parameters of the signal are DeltaH(ml) congruent to 1.4 - 1.6 mT; DeltaH(m2) congruent to 1 - 1.2 mT; DeltaH(m3) congruent to 0.6 - 0.8 mT and g(1) congruent to 2.020; g(2) congruent to 2.011; g(3) congruent to 1.99 and Hyper Fine Structure constant DeltaH(12) congruent to 2.1 mT; DeltaH(23) congruent to 5.3 mT. As the temperature increase from 77 K up to 293 K, the signal for g(4) congruent to 2.02 (DeltaH(m4) not congruent to 0.7 - 0.8 mT) appears and intensity of signals increase. It is also thought that the triplet observed at 77 K belongs to macroradicals of alkyl (-CH2-CH-CH2), alyl (similar toCH(2)CHCH = CHCH(2)similar to), carboanions and the acyl (HCO) radicals of the fourth signal. At room temperature, all the FR's transform into peroxide radicals. The total concentration of the FR's is minimum at 463 K and increases at the outlet of the extruder and the pipe sample. It is observed that the OIT (Qxygen Induction Time) values decrease as one approaches the outlet of the extruder (from 2030 to 10-15 minutes), while they increase for the processes of 433 K to 463 K. This event proves that the peroxide radicals form as one passes to room temperature. These results support those of the effects of the extrusion stage on the dynamic-mechanical characteristics [2]. Finally, FR's appear as a result of the breaking of the C-C bonds in the main polymer chains starting from the first step in the extrusion process (433 K) and in the later stages, due to the oxygen in the polymer structure, oxidation processes take place.
Keywords: Engineering; Polymer Science